2016
DOI: 10.15537/smj.2016.7.14335
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of the communication skills of residents in the Family Medicine Program in Central Saudi Arabia

Abstract: Objectives:To assess patients’ perceptions of the communication skills of family medicine residents.Methods:This is a cross-sectional study. Data were collected from patients, seeing 23 residents from 4 family medicine residency programs in Riyadh, Kingdom of Saudi Arabia namely, King Khalid University Hospital, Riyadh Military Hospital, Security Forces Hospital, and King Abdul-Aziz Medical City. The translated version of the Communication Assessment Tool (CAT) was used. Data were collected during January and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 8 publications
1
7
3
Order By: Relevance
“…One of the ndings of our investigation was that female gender is associated with better asking skills, whereas, in other components, there were no differences between female and male residents. This is contrary to past studies where Saudi patients rated male trainees higher than females (11). We also con rmed that older residents have higher scores in communication skills.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…One of the ndings of our investigation was that female gender is associated with better asking skills, whereas, in other components, there were no differences between female and male residents. This is contrary to past studies where Saudi patients rated male trainees higher than females (11). We also con rmed that older residents have higher scores in communication skills.…”
Section: Discussioncontrasting
confidence: 99%
“…Other studies have reported Family Medicine trainees are more skilled than Surgical trainees in providing information (18). It should also be noted that patients' perceptions of the communication skills of Family Medicine trainees in Saudi Arabia were shown to be relatively favorable in previous studies, however, this nding could not be replicated in the current study (11).This is an important nding that points towards gaps in specialty training in Family Medicine in the region and warrants further exploration. For pediatric trainees, there is inherent complexity around effective communication with patients and families (21).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The communication skills of a physician have a significant impact on patient health promotion and health education, especially in primary care practice where patients are first to come into contact with doctors (Alsaad et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The communication skills of a physician have a significant impact on patient health promotion and health education, especially in primary care practice where patients are first to come into contact with doctors (Alsaad et al, 2016). Levinson and Roter (1995) demonstrated that the psychosocial attitudes of primary care physicians are related to their communication behaviours.…”
Section: Discussionmentioning
confidence: 99%